Synthesising evidence of the effects of COVID-19 regulatory changes on methadone treatment for opioid use disorder: implications for policy. (March 2023) - Krawczyk, Noa; Rivera, Bianca D; Levin, Emily; Dooling, Bridget C E
Summary: As the USA faces a worsening overdose crisis, improving access to evidence-based treatment for opioid use disorder (OUD) remains a policy priority. Federal regulatory changes in response to the COVID-19 pandemic substantially expanded flexibilities on take-home doses for methadone treatment for OUD. These changes have fuelled questions about the effect of new regulations on OUD outcomes and the potential effect on health of permanently integrating these flexibilities into treatment policy going forward. To aide US policy makers as they consider implementing permanent methadone regulatory changes, we conducted a review synthesising peer-reviewed research on the effect of the flexibilities of methadone take-home policies introduced during COVID-19 on methadone programme operations, OUD patient and provider experiences, and patient health outcomes. We interpret the findings in the context of the federal rule-making process and discuss avenues by which these findings can be incorporated and implemented into US policies on substance use treatment going forward.